Early initiation of breast feeding practice among institutional delivered women in district Bareilly - Singh, Atul Kumar; Gupta, S. B.; Khan, Huma (International Journal Of Community Medicine And Public Health, 2017)
Background: A recent trial has shown that early initiation of breastfeeding could reduce neonatal mortality by 22%, which would contribute to the achievement of the Millennium Development Goals. Globally, over one million newborn infants could be saved each year by initiating breastfeeding within the first hour of life. In developing countries alone, early initiation of breastfeeding could save as many as 1.45 million lives each year by reducing deaths, mainly due to diarrheal disorders and lower respiratory tract infections in children. We studied the practice of early initiation of breast feeding among institutional delivered women in district Bareilly. Methods: This cross sectional study was conducted in the residence of 289 mothers who were delivered in health care institutions of district Bareilly. The study was carried out among women who delivered in 3 hospitals (one tertiary care hospital - SRMS IMS, one secondary level care hospital (district hospital) and one primary health center (PHC). All the recently delivered mothers were interviewed at their residences that were having infants aged up to 1 month. Results: 186 (64.4%) mothers had started the breast feeding within 1 hour after delivery. More than half (59.1%) women were aware about the duration of exclusive breast feeding while only 101 (34.9%) women aware about the correct positioning for proper breastfeeding. Conclusions: Early rooming-in, skin-to-skin contact and support to the mother are the simple interventions which are likely to have the greatest impact in reducing child mortality.